Exploring Classroom Management Techniques: Keys to Success in English Language Classroom - Joshi, Bhanu Bhakta (Journal of Jayaprithvi Multiple Campus, 2025)
Effective classroom management is a cornerstone of fruitful English Language Teaching (ELT), considerably prompting student engagement and learning outcomes. This research paper investigates effective classroom management techniques in ELT, stressing their role in fostering a conducive learning environment. Through analyzing approaches such as student motivation, relationship building with stakeholders, and discipline maintenance, this article explores their significance in an engaging and well-ordered classroom atmosphere. Employing a comprehensive appraisal of current practices and ideas of different scholars portrayed in their works, the study highlights how motivation nurtures a positive learning atmosphere, while robust relationships with students, parents, and colleagues contribute to a supportive educational community. Furthermore, the article examines strategies for preserving discipline that stimulate reverence and responsibility among learners. By incorporating these three key techniques, teachers can build vibrant and all-encompassing classrooms that not only facilitate language acquisition but also empower the students academically in multidimensional ways. The teachers employ a variety of teaching techniques in ELT classrooms based on the students’ diverse cultural and educational backgrounds along with the learning contexts, where this study finds these aforementioned techniques more effective for maintaining a learner-friendly classroom management. This paper aims to provide ELT practitioners with actionable intuitions to optimize their classroom management strategies for a more creative learning environment.